Allochthonous matter input in two different stretches of a headstream (Itatinga, Sao Paulo, Brazil) - Afonso, AAD; Henry, R.; Rodella, RCSM (Inst Tecnologia Parana, 2000)
In two streches of the Itauna stream, one in a gallery forest and the other in an herbaceous vegetation zone, litter matter input (sorted by leaves, ligneous and reproductive components) were measured during a year. In the gallery forest stretch, the direct input and lateral transport attained 713 g.m(-2).year(-1) and 421 g.m(-1).year(-1), respectively. In contrast, the herbaceous vegetation stretch showed a direct litter input and lateral transport of only 86 g.m(-2).year(-1) and 124 g.m(-1).year(-1), respectively. The empoverishment of riparian vegetation had a significant effect on the decrease of allochthonous input to stream mainly by direct input. Peaks of direct input into Itauna stream occurred during late dry season and in the early wet season. They were attributed to leaf fall from riparian trees and to enviromental conditions, such as wind. In March, which was the rainy season in this region, a peak of lateral transport was observed mainly in the herbaceous vegetation stretch, probably induced by runoff.
Keywords: allochthonous input; stream; riparian vegetation